2014
DOI: 10.1136/bmj.g6034
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding high and low patient experience scores in primary care: analysis of patients' survey data for general practices and individual doctors

Abstract: Objectives To determine the extent to which practice level scores mask variation in individual performance between doctors within a practice.Design Analysis of postal survey of patients’ experience of face-to-face consultations with individual general practitioners in a stratified quota sample of primary care practices. Setting Twenty five English general practices, selected to include a range of practice scores on doctor-patient communication items in the English national GP Patient Survey.Participants 7721 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 24 publications
2
56
0
Order By: Relevance
“…Previous research has demonstrated that the GP Patient Survey communication questions can differentiate between the performance of GPs and practices, as long as an adequate sample size is used to achieve acceptable statistical reliability. 129,141 This was confirmed by our simulation: with sufficient patient scores a strong correlation between patient ratings and competency will be observed. In the use of patient experience scores as quality indicators, our findings suggest that it is, therefore, possible to (1) trust aggregated patient scores that meet traditional standards of reliability as valid measures of comparative performance with respect to communication and (2) trust relatively low mean patient ratings.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous research has demonstrated that the GP Patient Survey communication questions can differentiate between the performance of GPs and practices, as long as an adequate sample size is used to achieve acceptable statistical reliability. 129,141 This was confirmed by our simulation: with sufficient patient scores a strong correlation between patient ratings and competency will be observed. In the use of patient experience scores as quality indicators, our findings suggest that it is, therefore, possible to (1) trust aggregated patient scores that meet traditional standards of reliability as valid measures of comparative performance with respect to communication and (2) trust relatively low mean patient ratings.…”
Section: Discussionsupporting
confidence: 68%
“…In line with previous work, we calculated communication scores by linearly rescaling responses between 0 and 100 and taking the mean of all responses when four or more informative answers were given. [129][130][131] Ratings by trained external raters…”
Section: Methodsmentioning
confidence: 99%
“…As per previous work, the authors calculated a doctor–patient communication score by linearly rescaling responses between 0 and 100 and taking the mean of all responses where four or more informative answers were given 20 , 31…”
Section: Methodsmentioning
confidence: 99%
“…A recent U.K. study indicates that variance between individual doctor communication scores could be greater than variance between practices. 29 Due to lack of separation between doctors in the patients' data, this effect could not be tested for in this study but could be investigated in subsequent studies. Also, the missing value rate varies considerably between items (Fig.…”
Section: Discussionmentioning
confidence: 90%